Protecting the bottom-line in a downturn - Schmidt-Gallas, Dirk (Henry Stewart Talks, 2009)
Dynamics in a distressed financial market, Investment income: a fickle friend, The disastrous impact of the volume hunt, Pricing in the most important profit driver of all, Introduction to power pricing, Value is created within the strategic triangle, What drives customer value?, Deriving the aggregated price-response function, Price experiments, What fees should be charged?, Preparing for the recovery